2022
DOI: 10.7759/cureus.27083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyaluronic Acid-Enriched Media in Embryo Implantation

Abstract: EmbryoGlue (Vitrolife, Sweden) is a hyaluronan-rich medium manufactured specifically for embryo transfer. Normally, culture media is used for embryo transfer. Culture media is enriched with albumin. Embryo transfer success depends upon the implantation rate. According to some researchers, hyaluronic acid-enriched media may be responsible for the success of embryo transfers. The aim of the study is to check the efficacy of hyaluronic acid-enriched media for previous in-vitro fertilization (IVF) failure patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…failures. [101] Valojerdi et al investigated the effectiveness of Em-bryoGlue in 417 patients as a human embryo transfer medium, reporting an increase in the clinical pregnancy and implantation rate in the tubal factors and repeated implantation failures. Furthermore, compared to 398 patients in the control group, these patients had considerably higher rates of live births and triplet deliveries.…”
Section: Embryo Transfer and Implantationmentioning
confidence: 99%
“…failures. [101] Valojerdi et al investigated the effectiveness of Em-bryoGlue in 417 patients as a human embryo transfer medium, reporting an increase in the clinical pregnancy and implantation rate in the tubal factors and repeated implantation failures. Furthermore, compared to 398 patients in the control group, these patients had considerably higher rates of live births and triplet deliveries.…”
Section: Embryo Transfer and Implantationmentioning
confidence: 99%
“…Also, the earlier studies demonstrate that the metabolism of glucose is a very important factor for sperm, and type 1 or type 2 diabetes can have harmful effects on the fertility of the male partner, especially on the quality of sperm cells, like motility, the integrity of sperm DNA, and the composition of semen [ 5 ]. There are many reasons for embryo transfer failure, including endometrial thickness, receptivity, embryo abnormalities, and inherited factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way of assessing sperm quality has been suggested: selecting suitable sperm based on its capacity to attach to HA [8]. A recent study has shown that using HA as a medium may have a greater beneficial effect on clinical pregnancy success [6]. PICSI works by choosing sperm based on the oocyte's affinity for HA, leading to higher ICSI success rates [10].…”
Section: Introductionmentioning
confidence: 99%
“…EmbryoGlue® (VitroLife, Sweden) is typically composed of hyaluronan (high concentration of HA (0.5 mg/mL)), a natural substance in the female reproductive tract, and other nutrients (low concentration of recombinant human albumin (rHA = 2.5 mg/mL)) supporting the embryo. The embryo glue is believed to improve the chances of successful implantation by helping the embryo adhere to the endometrium and promoting communication between the embryo and the uterine environment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%